The independence of the central bank and its role in the domination of financial capital over the State - Pierre-Manigat, Matari (2020)
The following work analyzes the role of the independence of the central bank in the relationship between the financial sector and the State at a theoretical level. In order to accomplish this task, the nature of the central bank is considered: the public institution, on the one hand, and the representative of the financial class, on the other hand. The duality determines the place of the bank in the machine of the State, as well as its relationship with the public Hacienda (or treasury). From a methodological focus that combines economy and political sociology, the links between the central bank and the public Hacienda that conform the organizational structure of the State, are highlighted. Its characterization is necessary in order to analyze the role of the State in the reproduction of a regime of accumulation. The “big crises” – or the crises of regimes of accumulation – determine the fundamental changes in the organizational structure of the State. The independence of the central bank became the litmus test for the reconfiguration of the structure of capitalism today. This is where the main conclusion of this work stems from: the organizational structure associated with the independence of the central bank operates like a transmission belt of financial domination in the State and the contemporary political arena.